Supplier Management System in Halal Food Supply Chain: A Case Study Approach - Tatsuya Fujiwara; Risyawati Mohamed Ismail (International Journal of Supply Chain Management, 2018)
Abstract The aims of this paper is to investigate supplier management in Halal food supply chain in according with an existing framework of supplier management and to explore how the size of enterprises influences supplier management in Halal food supply chain. In this study, the researcher adopted case study research method and collected the data from one small and medium-sized enterprise and one multinational enterprise producing Halal foods in Malaysia with Malaysia Halal certification. The findings showed specific risk consequences, supply risk sources, risk drivers and risk mitigating strategies in Halal food supply chain based on the framework of supplier management. By comparing the constructs of the framework, differences in the cases emerged: the type of risk mitigating strategies and the range of monitoring. Therefore, it is assumed that bargaining power and resources based on the size of enterprises influenced the type of risk mitigating strategies and the range of monitoring in Halal food supply chain. For future research, the researcher needs to take not only the size of enterprises but also other contextual factors into consideration for a wholesome approach in understanding each firms characteristics and how the supply chain system is affected.